Value of percutaneous needle biopsy of small renal tumors in patients referred for cryoablation. Issue 2 (4th March 2017) - Iguchi, Toshihiro; Hiraki, Takao; Gobara, Hideo; Fujiwara, Hiroyasu; Sakurai, Jun; Matsui, Yusuke; Araki, Motoo; Nasu, Yasutomo; Kanazawa, Susumu
Abstract: Purpose: To retrospectively evaluate the safety and diagnostic yield of needle biopsy of small renal tumors, and the clinical consequences of performing needle biopsy in patients referred for percutaneous cryoablation before their treatment. Material and methods: Biopsy was performed for 120 tumors (mean diameter, 2.2 cm) in 119 patients. All procedures were divided into diagnostic and non-diagnostic biopsies. Various variables were compared between the two groups. All cryoablation procedures were divided into two groups: procedures with or without simultaneous biopsy. The rates of benign or non-diagnostic tumors in each group were compared. Results: After performing 120 initial and eight repeat biopsies, Grade 1 bleedings occurred in 44 cases. Six tumors were non-diagnostic and 114 were pathologically diagnosed. There were no significant variables between the diagnostic and non-diagnostic biopsies. Unnecessary cryoablation was avoided in nine benign lesions by performing biopsy in advance. Cryoablation performed simultaneously with biopsy included significantly more benign or non-diagnostic tumors than cryoablation performed after biopsy (15.2% vs. 1.4%; p  = .01). Conclusions: Percutaneous biopsy of small renal tumors referred for cryoablation was a safe procedure with high diagnostic yield. The confirmation of pathological diagnosis prior to cryoablation is necessary because patients with benign tumors can avoid unnecessary treatment.